INCULCATING ECOLOGICAL SPIRITUALITY IN THE WORLDVIEW OF YOUNG PEOPLE IS THE DEMAND OF THE TIMES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Increasing the ecological spirituality of the mature generation is one of the main environmental problems of today [1-4].